O impacto do nível educacional dos prefeitos no IDEB: uma análise dos municípios do Nordeste - Correia, Antônio Welton de Sousa (2025)
This dissertation investigates the factors influencing educational performance in municipalities in the Northeast of Brazil, using the Basic Education Development Index (IDEB) as the dependent variable. The analysis considers socioeconomic and educational variables, including the educational level of mayors, GDP per capita, education spending, and characteristics of the local education system. The results show that the presence of graduated and female mayors is associated with improvements in the IDEB, highlighting the positive impact of qualified and inclusive leadership. Furthermore, GDP and education investments are strongly correlated with educational performance growth. The positive coefficient for graduated mayors suggests that having mayors with higher education is significantly associated with an increase in the IDEB scores of municipal school students. The analysis also reveals that female leadership in municipalities has a positive, though smaller, impact on educational outcomes. These findings support existing literature that highlights the importance of academic qualifications and the inclusion of women in municipal leadership positions in improving education quality. The evidence suggests that public policies focused on efficient management and strategic investments in education are crucial for improving educational outcomes in municipal schools. This dissertation contributes to the understanding of the factors shaping educational performance and provides valuable insights for future research and the formulation of educational public policies.